Pengaruh Pemberian Ekstrak Kulit Jengkol pada Pakan Terhadap Profil Darah Ikan Patin Siam (Pangasius hypophthalmus) - Setyawan, Agung Cahyo; Pramono, Taufik Budhi; Setiyaningsih, Lilik (Universitas Mataram, 2025)
Pathogenic bacteria are one of the main challenges in the cultivation of Pangasianodon hypophthalmus because they can cause organ damage and even death. The utilisation of natural ingredients such as Archidendron pauciflorum peel extract is one alternative to improve fish health in an environmentally friendly manner. This study aimed to evaluate the effect of adding Archidendron pauciflorum peel extract in feed on haematological parameters of Pangasianodon hypophthalmus. A total of 160 test fish were divided into four treatments with extract doses of 0% (control), 0.01%, 0.02%, and 0.03%, for 21 days. Parameters observed included total erythrocytes, haemoglobin levels, and haematocrit values. The results showed that Archidendron pauciflorum peel extract significantly increased haemoglobin levels and haematocrit values (P<0.05), especially at the 0.03% dose, compared to the control. Total erythrocytes showed a decrease on day 21 in all extract treatments, presumably due to the content of bioactive compounds (tannins, flavonoids, and saponins) in high doses. Bioactive compounds in Archidendron pauciflorum peel extract such as flavonoids, saponins, and tannins are known to play a role in improving haematological parameters, but their use needs to pay attention to the appropriate dose so as not to cause negative effects.